The Influence of E-Service Quality on Customer Loyalty Through Customer Satisfaction Among Livin' by Mandiri Users - Al Firdaus, Muhammad Yustan; Rachmawati, Indira (Universitas Pendidikan Ganesha, 2024)
Advances in information technology and the widespread proliferation of the internet have significantly changed service delivery. Banks are currently faced with demands to innovate in banking services and electronic services, particularly in the context of mobile banking. This study aims to analyze the impact of factors such as interface design, reliability, responsiveness, trust, and personalization on the level of customer satisfaction among Livin' by Mandiri application users. Data for this study was collected through the use of an online questionnaire distributed through Google Forms. This study used purposive sampling method for sample selection, with a sample size consisting of 408 customers using the Livin' by Mandiri application. Data analysis in this study was conducted using the SEM-PLS (Partial Least Squares) method. The results of this study show a significant positive relationship between factors such as interface design, reliability, responsiveness, trust, and personalization with customer satisfaction among Livin by Mandiri users. Furthermore, research findings show that customer satisfaction has a positive and significant effect on customer loyalty in the context of Livin by Mandiri. In addition, the study's findings reveal the significant positive influence of factors such as interface design, reliability, responsiveness, trust, and personalization on customer loyalty, with customer satisfaction acting as a mediator among Livin by Mandiri users.